2017
DOI: 10.1016/j.jfma.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial embolization as first-line rescue in intractable primary postpartum hemorrhage: Assessment, outcome, and subsequent fertility

Abstract: TAE was safe and effective in treating intractable primary PPH with a high success rate and preservation of menstruation and fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
0
13
0
9
Order By: Relevance
“…Related studies mostly support preservation of menstrual function and fertility following uterine embolization with gel foam, with one study reporting resumption of menses in all of their patients. Another study reported 98% preservation of menses and 82% successful future pregnancies (Touhami et al, 2014;Farouk et al, 2016;Cheng et al, 2017). Despite literature supporting preservation of fertility, gel foam poses some inherent disadvantages as an embolic agent for uterine AVM embolization compared to newer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies mostly support preservation of menstrual function and fertility following uterine embolization with gel foam, with one study reporting resumption of menses in all of their patients. Another study reported 98% preservation of menses and 82% successful future pregnancies (Touhami et al, 2014;Farouk et al, 2016;Cheng et al, 2017). Despite literature supporting preservation of fertility, gel foam poses some inherent disadvantages as an embolic agent for uterine AVM embolization compared to newer agents.…”
Section: Discussionmentioning
confidence: 99%
“…For genital bleeding following vaginal or caesarean delivery, or due to surgical complications including post hysterectomy (Cheng et al 2017 ; Lee et al 2012a ; Fu et al 2018 ), OHE should be considered, particularly if bleeding is due to spontaneous pseudoaneurysm rupture (Fig. 5 ) (Gonsalves and Belli 2010 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Permanent liquid embolic agents such as Cyanoacrylate or Onyx might be useful when a catheter cannot be passed to a sufficient distal location. However, time of polymerisation and liquid must be adjusted correctly and appropriate experience is needed (Cheng et al 2017 ; Lee et al 2012a ; Fu et al 2018 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Embolization makes it possible to avoid hysterectomy, while theoretically preserving the possibility of another pregnancy (5) . Cheng et al (31) described how menstruation and fertility could be preserved successfully for future pregnancy after embolization. Uterine artery embolization illustrates an important role in uterine fibroid and leiomyoma management.…”
Section: Clinical Anatomy Of Uterine Arterymentioning
confidence: 99%